English vocabulary in use : elementary (60 units of vocabulary reference and practice self-study and classroom use) - Mccarty, Michael; O'Dell, Felicity (Cambridge : New York : Cambridge University Press, 2005)
This top-selling vocabulary book is now available with a CD-ROM offering hundreds of completely new exercises. The CD-ROM has a built-in dictionary with full definitions and example sentences of key vocabulary. Students can listen to audio recordings, create their own tests and make personal notes within the dictionary. This edition 'with answers' is ideal for self-study.
Includes index.
Keywords: Vocabulary -- Problems, exercises, etc; English language -- Textbooks for foreign speakers; English language